Body Fluids in End-Stage Renal Disease: Statics and Dynamics - Kooman, Jeroen P. (Blood Purif, 2019)
BACKGROUND: Abnormalities in fluid status in hemodialysis (HD) patients are highly prevalent and are related to adverse outcomes. SUMMARY: The inherent discontinuity of the HD procedure in combination with an often compromised cardiovascular response is a major contributor to this phenomenon. In addition, systemic inflammation and endothelial dysfunction are related to extracellular fluid overload (FO). Underlying this relation may be factors such as hypoalbuminemia and an increased capillary permeability, leading to an altered fluid distribution between the blood volume (BV) and the interstitial fluid compartments, compromising fluid removal during dialysis. Indeed, whereas estimates of extracellular volume by bioimpedance spectroscopy are highly predictive of mortality, absolute BV assessed by the saline dilution technique was predictive of intra-dialytic morbidity. Changes in relative BV during HD are positively related to ultrafiltration rate (UFR) and, at least in some studies, negatively to FO. High UFR is also related to changes in central venous oxygen saturation (S(cv)O(2)), a marker for tissue perfusion. On the one hand, high UFR and more pronounced declines in S(cv)O(2), but on the other hand, flat relative BV curves are also predictive of mortality; the relation between outcome which statics and dynamics of fluid status appears to be complex. KEY MESSAGE: While technological developments enable the clinician to monitor statics and dynamics of fluid status and hemodynamics during HD in an accessible way, the role of technology-based interventions needs further study.